Penerapan Budaya Dayak Kenyah pada Interior Pendidikan Anak Usia Dini di Samarinda - Sherlia Sherlia (Intra, 2013)
Children are most valuable assets for the future of a nation. Therefore, the golden age of their development should not be abandoned. One of the ways to develop the children’s golden age is through Early Childhood Education which curriculum focuses on arranging and equipping classroom. The early childhood education interior design in Samarinda also introduces Dayak Kenyah culture to children so they can learn to preserve their local culture. By the implementation of central system, children are able to develop their talent and interest other than the academic.The methodology of the design starts from the method of gathering data containing data on field, literature data, and tipology data. The next step is observation through interview and study observation on similar object and finally analysis methodology like programming to the final design. By that process, the interior design refers to the variety of Dayak Kenyah Culture reflected on lamin, Dayak tribe long house.The dances culture becomes a theme for every central in order to have different atmosphere and form, starting from door decoration, furniture’s shape, and also materials adjusted with its central. Dayak tribe is closely associated with nature so the materials mostly used are wood texture. In order to make modern element, some parts of the wall use glasses, the floor combines tile and mosaic. The mosaic uses primary colours that can be found in Dayak Ornament to fit for the children. The application of Dayak Kenyah culture forms to this interior can stimulate the art and culture creativity on the children golden age.